ANALYSIS OF THE POTENTIAL OF THE COASTAL VILLAGE OF KARANGAGUNG, TUBAN REGENCY FOR VILLAGE ECONOMIC GROWTH THROUGH BLUE ECONOMY FACTORS - Anggapratama, Reza (JURNAL ECONOMICA : Research of Economic And Economic Education, 2024)
The impact of globalization on the emergence of the idea of sustainable growth or Sustainable Development Goals (SDGs) was introduced by the United Nations (UN) on September 25 2015. The cycle of economic activity that sustainably utilizes marine and coastal resources is outlined in the blue economy. This research aims to assess the potential of the coastal village of Karangagung, Tuban Regency, in achieving sustainable economic growth goals related to marine ecosystems and to determine the challenges in managing this potential through the application of blue economy factors. Blue economy factors include workforce (X1), capital (X2), technology (X3) and income (X4). The research method uses a mixed method. Mix methods are a combination of quantitative and qualitative research. The quantitative method uses multiple linear regression analysis. Questionnaires were distributed to 355 respondents. Qualitative method through FGD and interviews. The research results show that it partially influences village economic growth with an F-count of 2138.583 > 3.02. The results simultaneously show that workforce with a value of 0.000, capital with a value of 0.003, technology with a value of 0.000 and income with a value of 0.000 affect village economic growth. The results of the coefficient of determination with a value of 96.1% show that workforce, capital, technology and income influence village economic growth. The results of FGDs and interviews with fishermen and village officials show that workforce, capital, technology, and income influence village economic growth because most Karangagung village residents earn their livelihood as fishermen, influencing the village's economic growth.